Measuring the impact of dental service quality on revisit intention using an extended SERVQUAL model - Sharka, Rayan; Sedayo, Lamer; Morad, Majd; Abuljadayel, Jameel (Frontiers in Oral Health, 2024)
Background The pursuit of quality services can lead to both service enhancement and increased motivation to visit dental centers for oral health treatment. Aims The purpose of this study is to investigate the effect of dental center service quality factors on revisit intention among adult patients by applying an extended service quality model (SERVQUAL). Methods This cross-sectional study was conducted between September and November 2023 in the outpatient waiting areas and clinical settings of Umm Al-Qura University Dental Teaching Hospital (UQU-DTH). A sample of 355 patients was invited by the convenience sampling method. The data was collected through a validated Arabic version of the extended SERVQUAL questionnaire. A hierarchical regression analysis was used to assess the incremental effects of the extended SERVQUAL factors on the intention of patients to revisit the UQU-DTH while controlling for demographic variables. Cronbach alpha was used to examine the internal consistency of each model factor. Results A total of 330 completed responses were received, with a 93% response rate. The findings indicated that demographic variables such as age and level of education contribute to some extent but become negligible when the extended SERVQUAL factors are included in the model. Moreover, the extended SERVQUAL model factors substantially improved the model. Three factors were found to positively and significantly affect the revisit intention, namely, “staff-related factors,” “cost-effectiveness,” and “responsiveness.” Overall, the model explained 65.6% of the variance in the revisit intention (R2 = 0.656, p < 0.001). Conclusion The findings present a unique model that may be used to better understand the factors that influence patients' intentions to revisit dental centers in an educational setting. Additionally, it identified elements that dental center quality management needs to prioritize and address.